Behaviour of dispersion indices in pattern detection of a population of angico, Anadenanthera peregrina (Leguminosae) - Malhado, A. C. M. [UNESP]; Petrere Jr., M. [UNESP] (Instituto Internacional de Ecologia, 2004)
Neste trabalho calculamos os valores de oito índices de detecção de padrões, usando quadratins de tamanhos diferentes, onde indivíduos de angico com mais de 1,5 m estavam localizados, a fim de examinar seus comportamentos estatísticos com o aumento do tamanho da amostra. Conclui-se que o melhor índice é de Morisita padronizado (Ip), o qual é independente do tamanho da amostra.

In this paper we calculate the values of eight pattern detection indices, using different quadrat sizes where individuals of angico above 1.5 m were located, in order to examine their statistical behaviour with increasing sample size. It was concluded that the best index is the standardized Morisita index (Ip) which is completely independent of sample size.
Padrão de agregação do angico Anadenanthera peregrina
Keywords: padrão espacial; agregação; angico; Anadenanthera peregrina; spatial pattern; aggregation; angico; Anadenanthera peregrina